Analisis Morfologi Ikan Puntius binotatus Valenciennes 1842 (Pisces: Cyprinidae) dari beberapa Lokasi di Sumatera Barat - Dwinda K Fitri; Dewi Imelda Roesma; - Syaifullah (Jurnal Biologi Universitas Andalas, 2012)
The morphological analysis of Puntius binotatus Valenciennes 1842 (Pisces: Cyprinidae) collected from several locations in West Sumatra has been conducted from April to June 2012. Several morphological characters were measured and analyzed using principal component analysis (PCA) and UPGMA. This study found significant morphological variations of the standard length (SL), head length (HL), least depth of caudal peduncle (HCPD), length of caudal peduncle (LCPD), eye diameter (ED), caudal fin length (CFL), caudal fin length up (CFL up), caudal fin length bottom (CFL bottom), length of maxillary barbels (LMB) and length of snout barbels (LSB). Those variations were more likely influenced by elevations and western-eastern side of Barisan Mountain in Sumatra.Keywords: Barisan Mountain, cyprinidae, morphological characters, P. binotatus